Influence of Variation in Nitrogen Fertilizer dose Towards Yields and Protein Level of White Corn Anoman Variety - Safira - Nim: 11414024 , Dini
Corn is the third important food commodity in the world after rice and wheat. White corn development still not widely developed because it was once popular as a staple food in some areas but its popularity declined. This is due to farmersÃ‚Â’s interest in planting white corn reduced and more interested in hybrid yellow corn that has higher productivity. Increasing competitiveness of white corn requires increasing productivity and increasing its nutritional content. Research conducted at ITB Jatinangor farmland in October 2017 to February 2018 and Biomass Production Systems Engineering Laboratory in January to May 2018. Research using Randomized Blocked Design with 5 treatments and spread into 5 group repetition. The treatments are nitrogen fertilizer dose as A: 250 kg/ha, B: 300 kg/ha, C: 350 kg/ha, D: 400 kg/ha, E: 450 kg/ha. Based on this research, nitrogen fertilizer doses have no real effect against yield and protein level of white corn Anoman variety but 250 kg/ha nitrogen fertilizer likely to give better yield on weight od corn cobs per plant, length of corn cobs per plant, number of seeds per corn cob, and weight of seeds per plant.